Terroir Influence on Water Status and Nitrogen Status of non-Irrigated Cabernet Sauvignon (Vitis vinifera). Vegetative Development, Must and Wine Composition (Example of a Medoc Top Estate Vineyard, Saint Julien Area, Bordeaux, 1997) - Chone, X.; Van Leeuwen, C.; Chery, P.; Ribereau-Gayon, P. (South African Journal of Enology and Viticulture, 2017)
Terroir effect on vine vigour, must composition and wine quality was investigated for Cabernet Sauvignon during a rainy vintage in a top estate of the Medoc area (Bordeaux, France). Soil was the only variable in this survey. Vine water status was determined by means of leaf water potential. Mild water deficits were observed only on a gravelly soil with a shallow root zone. Vine nitrogen status was determined by total must nitrogen content.  Nitrogen status varied from deficient to unlimited. Nitrogen deficiency reduced vine vigour to a greater extent than did mild water deficits. The smallest berries, as well as the highest phenolic content for both must and wine, were observed under nitrogen deficiency. Both early mild water deficits and a nitrogen deficiency throughout the growth period were demonstrated to have beneficial effects on the phenolic content of berries and on wine quality. 1\vo combinations of vine water status and vine nitrogen status led to the most highly appreciated wines: a low nitrogen status without water deficits and a medium nitrogen status accompanied by mild water deficits.